The value relevance of key audit matters - Sacco, Fabrizio (My University, 2020)
Key audit matters (KAMs) are a disclosure requirement per the International Standards on Auditing (ISA) 701 for companies listed on the Johannesburg Stock Exchange (JSE). KAMs relate to those matters encountered during the audit which were of most significance, and which must be disclosed separately in the audit report. The current literature on KAMs is primarily of a qualitative nature. This dissertation attempts to contribute to the existing literature by providing a quantitative lens to the value relevance of KAMs. The objective of KAM paragraphs in audit reports is to provide more relevant information to users of the report. To assess this objective, a value relevance study was conducted to evaluate whether KAM disclosures were providing relevant information to users of the audit report. The data used in the study were collected from the annual reports of the companies within the sample. The market to book ratio of a firm was used as a proxy for value relevant information. A multiple regression was conducted to investigate whether the number of KAMs or category of KAMs were value relevant to users of the audit report. The findings in the research indicate that the number of KAMs disclosed in the audit report is not seen as value relevant, whereas categories of KAMs relating to the profitability and cash flows of the firm were identified as value relevant. Future research could assess KAM disclosures relating to companies not primarily listed on the JSE, as well as unlisted and public sector entities
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (in the field of Accounting), University of the Witwatersrand, 2020